RESEARCH OF AUTOGENERATOR PARAMETRIC TEMPERATURE SENSORS - OSADCHUK, JAROSLAV; OSADCHUK, ALEXANDER; OSADCHUK, VLADIMIR (Herald of Khmelnytskyi National University. Technical sciences, 2022)
Autogenerator parametric temperature sensors based on transistor microelectronic structures with negative differential resistance with primary transducers such as thermistors and thermodiodes are proposed, and the primary thermosensitive elements are active elements of sensor autogenerator circuits, which simplifies their design. Based on the consideration of physical processes in primary heat-sensitive transducers and autogenerators of sensors, mathematical models of temperature sensors have been developed, on the basis of which parametric dependences of transformation and sensitivity functions are obtained. It is shown that the main contribution to the conversion function is made by temperature. This causes a change in the equivalent capacitance and negative differential resistance of the sensor autogenerators, which in turn changes the output frequency of the temperature sensors. The sensitivity of the temperature sensors varies from 1.2 kHz/0C to 2.35 kHz/0C when the temperature changes from 0 0C to 125 0C. The obtained parametric dependences of temperature sensor conversion functions show the possibility to obtain basic sensor characteristics much easier and clearly demonstrate the influence of each parameter of primary converters and autogenerator elements on sensor output frequency in comparison with calculations of conversion functions from equivalent device circuits based on Kirchhoff equations solution. Frequency output temperature sensors do not require analog-to-digital converters and amplifiers for further processing of information signals, which reduces the cost of information and measuring equipment, in addition, it is possible to transmit information over distances when operating sensors at ultrahigh frequencies.